ENT 530 Social Media Portfolio: Mouthgasm Crunchy by Akashah / Muhammad Nur Akashah Mazlan - Mazlan, Muhammad Nur Akashah (2021)
Mouthgasm Crunchy is a brand that I took part in becoming one of their agents. The main platform that I used for this business is Facebook. I have created the Facebook page for the business and manage the page by applying the method that I have learned. The type of product that I promoted on my page is a type of snack that has been viral for quite some time. I also provide a delivery service using a third-party courier to deliver the product to our customers, but the delivery covers the areas that are only in Malaysia. Mouthgasm Crunchy offer scrumptious and flavorful choco jar fuses with coffee flavour to create unique and high class flavour which suit Malaysian taste at affordable price. On my Facebook Page, information on the product such as price and weight are being stated to allow the customer to gain the necessary information to know what kind of product we offer. Facebook Page is the main requirement to accomplish this assignment as it becomes the core of the assignment. Facebook Page creation is easy, simple and convenient especially for the new users as Facebook provides guidance on the process itself. I have utilized the page features such as messenger buttons allowing the customer to directly message to ask about the product or to order the products or even allowing customers to give feedback on our product and services. Lastly, using Facebook as a main platform for a new business is actually an efficient way because Facebook itself is a big social media platform that has a lot of users all around the world. Creating an interesting page to promote our product allows us to attract a lot of users who can become our customers. I have applied all the methods that I have learned, and it is really efficient and helpful for me to create and to promote my business.